Low-Frequency Oscillation Suppression Strategy for Power System Based on Supplementary Damping Control of Compressed Air Energy Storage - Kangkang WANG; Xinwei SUN; Bo ZHOU; Tianwen ZHENG; Wei WEI; Libo JIANG (Zhongguo dianli, 2023)
With significant increase of penetration of electronic equipment in the power system, the low-frequency oscillation problem of the power system under disturbance are becoming increasingly prominent. Therefore, combined with the good active power regulating ability of compressed air energy storage, a low-frequency oscillation suppression strategy is proposed based on the supplementary damping control of compressed air energy storage. Firstly, a mathematical model of compressed air energy storage is established, and the influence of the mass flow on its output power is analyzed. Secondly, the feasibility of compressed air energy storage to suppress low-frequency oscillation is analyzed, and a supplementary damping controller based on regulating valve is proposed to adjust the mass flow. And then, the output power of the compressed air energy storage is controlled to suppress the low-frequency oscillation of the power grid. Finally, a power system simulation model of 4-generator and two-area with compressed air energy storage is established to verify the effectiveness and feasibility of the proposed method. The simulation results show that the proposed method can provide positive damping for the power grid, and can rapidly suppress the low-frequency oscillation of the power grid and effectively improve the stability of the power system.